Does High-Intensity Endurance Training Increase the Risk of Atrial Fibrillation?: A Longitudinal Study of Left Atrial Structure and Function. (May 2018) - Opondo, Mildred A.; Aiad, Norman; Cain, Matthew A.; Sarma, Satyam; Howden, Erin; Stoller, Douglas A.; Ng, Jason; van Rijckevorsel, Pieter; Hieda, Michinari; Tarumi, Takashi; Palmer, M. Dean; Levine, Benjamin D.
Abstract : Background: Exercise mitigates many cardiovascular risk factors associated with atrial fibrillation. Endurance training has been associated with atrial structural changes which can increase the risk for atrial fibrillation. The dose of exercise training required for these changes is uncertain. We sought to evaluate the impact of exercise on left atrial (LA) mechanical and electrical function in healthy, sedentary, middle-aged adults. Methods: Sixty-one adults (52±5 years) were randomized to either 10 months of high-intensity exercise training or yoga. At baseline and post-training, all participants underwent maximal exercise stress testing to assess cardiorespiratory fitness, P-wave signal-averaged electrocardiography for filtered P-wave duration and atrial late potentials (root mean square voltage of the last 20 ms), and echocardiography for LA volume, left ventricular end-diastolic volume, and mitral inflow for assessment of LA active emptying. Post-training data were compared with 14 healthy age-matched Masters athletes. Results: LA volume, Vo2 max, and left ventricular end-diastolic volume increased in the exercise group (15%, 17%, and 16%, respectively) with no change in control ( P <0.0001). LA active emptying decreased post-exercise versus controls (5%; P =0.03). No significant changes in filtered P-wave duration or root mean square voltage of the last 20 ms occurred after exercise training. LA and left ventricular volumes remained below Masters athletes. The athletes had longer filtered P-wave duration but no difference in the frequency of atrial arrhythmia. Conclusions: Changes in LA structure, LA mechanical function, and left ventricular remodeling occurred after 10 months of exercise but without significant change in atrial electrical activity. A longer duration of training may be required to induce electrical changes thought to cause atrial fibrillation in middle-aged endurance athletes. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique Identifier: NCT02039154.